Trashumancia, Espacio para Poesía y Arte : enero-abril 1994 - Ocaranza, Jorge Octavio (dirección); Orendain, Jorge (coordinación) (Trashumancia, 1994)
Contiene obra de: José Javier Coz, Lalo Quimixto, Brianda Domecq, Sergio Briceño González, Víctor Manuel Pazarín, Pedro Angel Palou, Jorge Valencia, Mario Antonio Calderón, Margarita Valdivia Avila, Adriana Martínez Sánchez, Antonio A. Guerrero Hernández, Armando Alonso, Juan Pablo de Avila, Fabián Muñoz, Jorge Castillo, José de Jesús Lara Huerta, Rubén Chávez Ruiz Esparza, José Luis Engel, Elizabeth Dalziel, Fernando Franco, Gabriel Figueroa, Hugo Gutiérrez Vega, Irma Peiro, Jorge Díaz Barajas, José Ramos, Luis Sánchez Villaseñor, Juan Gelman, Gabriel Trujillo, Raúl Aceves, Ramiro Lomelí, Raúl Vázquez, Teresa Blanco y Saúl Irigoyen.